2014
DOI: 10.1364/ol.39.000343
|View full text |Cite
|
Sign up to set email alerts
|

Generation and erasure of femtosecond laser-induced periodic surface structures on nanoparticle-covered silicon by a single laser pulse

Abstract: We experimentally show that the generation and erasure of femtosecond laser-induced periodic surface structures on nanoparticle-covered silicon inducted by irradiation with a single laser pulse (800 nm, 120 fs, linear polarization) depend on the pulse fluence. We propose that this is due to competition between periodic surface structuring originating from the interference of incident light with surface plasmon polaritons and surface smoothing associated with surface melting. Experimental results are supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…This transition has been extensively studied before with the parameters λ = 800 nm and τ D = 1.1 fs, corresponding to γ/ω = 0.39. 9,13,18,23,24 The evolution of the Fourier transforms along both k x = 0 and k y = 0 axes as ω p /ω grows for γ/ω = 1 is shown in Figure 4. These are two orthogonal slices of the correspong two-dimensional calculations of Figures 3(a) -(f).…”
Section: A Formation Of C-lipsssmentioning
confidence: 99%
“…This transition has been extensively studied before with the parameters λ = 800 nm and τ D = 1.1 fs, corresponding to γ/ω = 0.39. 9,13,18,23,24 The evolution of the Fourier transforms along both k x = 0 and k y = 0 axes as ω p /ω grows for γ/ω = 1 is shown in Figure 4. These are two orthogonal slices of the correspong two-dimensional calculations of Figures 3(a) -(f).…”
Section: A Formation Of C-lipsssmentioning
confidence: 99%
“…A possible explanation for this phenomenon might be that the morphology of NPs could be changed by the melting effect. To confirm this, the two‐temperature model is utilized to calculate the electron temperature and lattice temperature of NPs: CetTe=ke2TeGelTeTl+Sr,t CltTl=GelTeTlwhere T e and T l represent the electron and lattice temperatures; C e and C l are the electron and lattice heat capacities; S ( r , t ) is the laser heat density; in the meanwhile, k e and G el denote the electron thermal conductivity and electron–phonon coupling factor, respectively. As shown in Figure 3c, the thermalization between the carrier and the lattice system is reached in 15 ps when the laser fluence is 0.002 J cm −2 .…”
Section: Information About Sample Preparationmentioning
confidence: 99%
“…Single-pulse irradiation can provide fundamental information of fs laser-matter interaction, which is important for investigating the origin of an LSFL [18][19][20] . Murphy et al fabricated Au micro-disks 110 nm thick on Si substrates, and studied the formation of periodic ripples near the Au-Si edges after irradiation of a single fs laser pulse.…”
mentioning
confidence: 99%
“…By changing the laser polarization orientation, they found that the LSFL formation was dominated by SPPs excitation or by Fresnel diffraction [18,19] . Yang et al studied the generation and erasure of periodic ripples on nanoparticlecovered silicon induced by a single fs pulse with a different laser fluence, and found that these phenomena were due to the competition between periodic surface structuring originated from the interference of the laser field and SPPs and surface smoothing associated with surface melting [20] . The above references focused on the mechanisms of the LSFL formation on semiconductors by using the surface micro/nanostructures as defects after the irradiation of a single pulse.…”
mentioning
confidence: 99%
See 1 more Smart Citation